The Impact of Oxidative Stress on Adipose Tissue Energy Balance - Masschelin, Peter M.; Cox, Aaron R.; Chernis, Natasha; Hartig, Sean M. (Frontiers in Physiology, 2020)
Overnutrition and sedentary activity reinforce the growing trend of worldwide obesity, insulin resistance, and type 2 diabetes. However, we have limited insight into how food intake generates the complex metabolic perturbations associated with obesity. Accumulation of mitochondrial oxidative stress contributes to the metabolic changes in obesity, but the mechanisms and significance are unclear. In white adipose tissue (WAT), mitochondrial oxidative stress and the generation of reactive oxygen species (ROS) impact the endocrine and metabolic function of fat cells. The central role of mitochondria in nutrient handling suggests pharmacological targeting of pathological oxidative stress likely improves the metabolic profile of obesity. This review will summarize the key pathogenic mechanisms of obesity-driven oxidative stress in WAT.